Biofilms in Wastewater Treatment: A Systematic Review of Biological Design and Efficiency - Ananta, Yorasakhi; Fitri, Salsabila Dwi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
Biofilms are essential in modern biological wastewater treatment systems due to their unique structural and functional capabilities. This systematic review explores the role of biofilms in enhancing the efficiency of wastewater treatment, focusing on design considerations and microbial interactions. The review compiles and synthesizes data from recent studies to understand how biofilms contribute to pollutant removal, operational stability, and energy efficiency. Key findings indicate that biofilm-based systems, such as trickling filters, rotating biological contactors (RBC), and membrane bioreactors (MBR), offer superior contaminant degradation due to high microbial density and resilience. The study highlights future opportunities for optimizing biofilm engineering to meet environmental and regulatory challenges.